POSSIBILITIES OF IMPROVING THE SHEAR STRENGTH BETWEEN DIFFERENT TYPE OF CEMENT AND ZIRCONIA CERAMICS: LITERATURE REVIEW - Ivan Gerdzhikov; Elka Radeva; Todor Uzunov (Peytchinski Publishing, 2021)
Background: Zirconia ceramics are a modern dental material which has a wide range of application in restoration of frontal and distal teeth. This is due to its improved mechanical properties and aesthetics. Aim: This literature review analyses the possibilities for improvement of the bond strength between zirconia ceramics and different types of cement which are used for fixation of prosthetic constructions. Review Results: The evidence from the literature indicates that preliminary treatment of zirconia ceramics increases the bond strength significantly to the cement. In this respect, different methods and materials are used for the treatment of the zirconium dioxide surface. Some of them include only mechanical treatment with diamond burs, a different type of lasers and sandblasting with aluminum oxide. Other methods have chemical action by the use of hydrofluoric acid and fluoride compounds. According to some data, zirconium structure does not allow etching which leads to application of different type of primers for increasing the shear strength. Studies show that silane application significantly improves the shear bond strength to the cement, as well as, zirconium tensile strength. Optimal results are registered with a combination of treatment with mechanical methods and silane application. Conclusion: Preliminary mechanical and chemical treatment of zirconia surface improves the shear bond strength considerably to the cement. The variety of surface treatment methods complicates the establishment of a standard protocol for fixation of zirconium prosthetic constructions.